2013
DOI: 10.1126/scisignal.2003405
|View full text |Cite|
|
Sign up to set email alerts
|

Inositol Polyphosphate Multikinase Is a Coactivator of p53-Mediated Transcription and Cell Death

Abstract: The tumor suppressor protein p53 is a critical stress response transcription factor that induces the expression of genes leading to cell cycle arrest, apoptosis, and tumor suppression. We found that mammalian inositol polyphosphate multikinase (IPMK) stimulated p53-mediated transcription by binding to p53 and enhancing its acetylation by the acetyltransferase p300 independently of its inositol phosphate and lipid kinase activities. Genetic or RNA interference (RNAi)–mediated knockdown of IPMK resulted in decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…2F) and the percentage of metastases to liver (Fig. 2G), the most common site of metastasis for The inositol polyphosphate kinases, including IP6Ks, have both catalytic activity-dependent and -independent functions (1,5,11,27,28). To examine whether the oncogenic actions of IP6K2 depend on its catalytic activity, we established rescue cell lines by retroviral expression of wild-type (WT-R) or kinase-dead K222A IP6K2 (29) (KD-R) in IP6K2 −/− cells.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…2F) and the percentage of metastases to liver (Fig. 2G), the most common site of metastasis for The inositol polyphosphate kinases, including IP6Ks, have both catalytic activity-dependent and -independent functions (1,5,11,27,28). To examine whether the oncogenic actions of IP6K2 depend on its catalytic activity, we established rescue cell lines by retroviral expression of wild-type (WT-R) or kinase-dead K222A IP6K2 (29) (KD-R) in IP6K2 −/− cells.…”
Section: Significancementioning
confidence: 99%
“…IP6K1 and IP6K2 are widely distributed, whereas IP6K3 is expressed primarily in the brain (9). A related enzyme, inositol polyphosphate multikinase (IPMK), converts IP3 to IP4 and IP5, displays physiologic PI3 kinase activity (10), and noncatalytically acts as a transcriptional coactivator (11) and stabilizer of the mTOR complex-1 (12). Whether IP6Ks and IPMK play direct roles in tumor progression remains unexplored.…”
mentioning
confidence: 99%
“…Whereas IPMK's ability to regulate transcription in yeast is well-established, nuclear roles of mammalian IPMK are less understood. We recently reported that IPMK binds to p53 during cell death and enhances p53-mediated gene transcription independent of IPMK catalytic activity (17,18). Blind et al (23) showed that IPMK's nuclear PI3 kinase activity generating PIP3 is integral to the transcription of steroidogenic factor 1 targets (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IPMK displays physiologic activities that are independent of its catalytic activity, such as binding and stabilizing the mTOR1 complex (16), as well as enhancing p53-mediated transcription and cell death (17,18). We show that IPMK is a transcriptional coactivator that is required for induction of a multiplicity of IEGs in the brain by binding to and regulating the recruitment of the histone acetyltransferase CBP.…”
mentioning
confidence: 97%
“…Furthermore, IPMK displays functions independent of its kinase activity. It binds and stabilizes the mTOR complex (16) and serves as a transcriptional coactivator for CREB-binding protein (17), p53 (18), and serum response factor (19). Despite these insights into the functions of IPMK, its physiologic and pathologic regulation have been largely unexplored.…”
mentioning
confidence: 99%